The gadzingo: towards a Karanga expansion matrix in 18th- and 19th- century Southern Zimbabwe - Mazarire, Gerald C. (2016)
The territorial boundaries of Zimbabwe's pre-colonial people have remained elusive to successive generations of political administrators and scholars alike. The lack of appreciation of the material, physical and symbolic attributes informing local principles of territoriality has condemned any analysis of these African boundaries to exercises in futility. This paper discusses the explicit details of a formula used to define these concepts amongst the Karanga of southern Zimbabwe in a specific time context that gave rise to a political culture based on an elaboration of established centre–periphery models. The gadzingo was not only a formula of expansion and fragmentation from central cores, but also a cohesive element facilitating the existence of discrete political entities that can be positively and physically identified in the historical record